PENGARUH PEMANFAATAN AUDIO VISUAL DALAM MENINGKATKAN KEMAMPUAN KONGNITIF PESERA DIDIK - Nur Ayna; Sunarwin Sunarwin; Magdalena Dhema (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
Problem solving abilities is purpose to knows the injhuenca of using andro visual in cognitve increasing of student. This research implemented in SMA Negeri 1 Talibura on semester two mi periodof 2019/2020. The populasion of this research is all the student of SMA Negeri I Talibura where the sample of the research is the student of ten class mia which 51 student with is class of mia 1 and class mia II. The interpretation of the sample is using tehnigve. This research as aform , of transparant eksperiment type with the design. The tehinige of data collection sheert and test. This research using analysis data technigne,thent is normality test homogenenity test and t-test. Normality test data refers to the data tosttribube with normaly and homogenity that is the data is homogen. Based on hypothesis testing using the t-test shows that the value of tcount = 3.14, while ttable = 2.00. This shows that the value of tcount > ttable so that. it can be concluded that the audio visual media inflecaned to abblity of congnitive of the student of SMA Negeri I Talibura.